Analysis of Level of Service and Quality of Service of shared Bicycle lane of Lalitpur- A case study of Kupondole to Lagankhel road section - Sahan Sundar Baidya; Gopal Gautam (Journal of Innovations in Engineering Education, 2024)
As used in the all the major European countries, bicycle is the major transport vehicle used for urban mobility due to its environmental, social and economic benefits. The cycle lane of the Lalitpur was made as the shared cycle lane which prioritizes the cycle users first and then it can be shared by other vehicles as well. But this concept faced various criticisms as it is not considered safe, especially in the route of Lalitpur which accommodates large number of other traffic volume. In this case the performance measure of the shared cycle lane is necessary. This study uses Level of Service (LoS) and Quality of service (QoS) approach to evaluate the performance of the shared cycle lane. Empirical formula developed by Nayak [1] was used to calculate the LoS by collecting the necessary traffic volume data and other parameters and QoS analysis was done by collecting the perceptional data. The LoS of Kumaripati and Lagankhel was found to be worst in comparison with the fairly similar LoS of other study areas. And by using the QoS approach, the variables such as road safety, network connectivity, traffic pollution, pavement surface, sign post, road marking, conflict due to parked cars and conflict due to bus stop were found to be the most significant ones in influencing the quality of service.